2022
DOI: 10.1007/s00704-022-03991-z
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the spatiotemporal variations and mechanisms for the near-surface wind speed over China in the last 40 years

Abstract: Near-surface wind speed is of great signi cance in many aspects of the human production and living.This study analyses the spatiotemporal characteristics of the near-surface wind speed and wind speed percentiles with meteorological station observations in China from 1979 to 2019. Furthermore, the mechanisms of the wind speed variations are also investigated with ERA-Interim reanalysis dataset.Spatially, the wind speeds in the northern and eastern regions of China are larger than that in the central and souther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…It is also mentioned in several excellent papers referenced in this paper that, in the Chinese region, it is found that the spatiotemporal variability in wind resources in China is apparent and northeast China has the highest wind potential [17]. In addition, significant results show that the larger near-surface wind speed mainly occur in the northern and eastern regions, the Tibetan Plateau, and the Western Pacific zones in China [20]. This is consistent with the wind resources studied in this paper and verifies the accuracy of the text.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It is also mentioned in several excellent papers referenced in this paper that, in the Chinese region, it is found that the spatiotemporal variability in wind resources in China is apparent and northeast China has the highest wind potential [17]. In addition, significant results show that the larger near-surface wind speed mainly occur in the northern and eastern regions, the Tibetan Plateau, and the Western Pacific zones in China [20]. This is consistent with the wind resources studied in this paper and verifies the accuracy of the text.…”
Section: Discussionsupporting
confidence: 51%
“…According to the literature cited in this paper, annual surface wind speed (SWS) decreased from 1980 to 2012, with human activities being the most likely reason for the drop, while the improvement in the Asian meridional circulation was a key factor in the increase in SWS in winter [16]. Moreover, prior research has discovered a significantly decreased near-surface wind speed trend in China from 1979 to 2019, particularly between 1979 and 1996 [20]. The multi-year average wind speed showed a decreasing trend before 2010 and an increasing trend after 2010, when the study area and time range of this paper were combined [35].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies pointed out that the stilling wind speed is caused by the significantly decreasing high-level wind speed, which is related to the weakening large-scale atmospheric circulation (Gastineau and Soden, 2009), such as atmosphere-ocean circulation (Zha et al, 2021) and Arctic oscillation (AO, Ge et al, 2021). The weakening large-scale circulation may be because high latitudes warm faster and more significantly than other areas, resulting in reduced differences of temperature and pressure between high and low latitudes (Li et al, 2022). Other studies argue that the weakening wind speed is related to significant changes in land-surface conditions, including changes in land-use type (Deng et al, 2021) and urbanization (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The prevailing wind direction is northnorthwest. Dust and sand storm occurs centrally between March and May, and days with wind greater than 17 m s −1 were approximately 10 d per year (Li et al 2022). Basic soils mainly are aeolian sandy soils, light brown soils and gray desert soils.…”
Section: Study Areamentioning
confidence: 99%